Supercritical CO2 Power Technology: Strengths but Challenges - Michel Molière; Romain Privat; Jean-Noël Jaubert; Frédéric Geiger (Energies, 2024)
In the late 1960s, a handful of inspired researchers predicted the great potential of supercritical CO2 (“sCO2”) cycles for the production of electricity and highlighted the prospects for dramatic reductions in component sizes and efficiency increases. Since then, considerable development programs have been deployed around the world to “tame” this new technology. Despite these efforts, in-depth engineering studies and extensive testing are still necessary today before viable designs can be released for large-scale industrial applications. This raises questions as to the reasons for this delay, this debate being rarely addressed in the current literature. This situation has motivated the present study. Trying to unravel such an intricate topic requires to understand the distinctive properties of supercritical CO2 and the particular requirements of closed, high-pressure power systems. This article aims then to provide a broad overview of sCO2 power cycles, highlighting their main advantages and limitations and reflecting the challenges associated with the industrialization of that technology which actually requires disruptive and innovative designs.